Skin-Related Neglected Tropical Diseases (Skin-NTDs)-A New Challenge - Asiedu, Kingsley (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue explores the range of clinical manifestations and epidemiology of both skin NTDs and common skin disease in endemic regions, the use of common diagnostic and management pathways, the different technologies that play a role in diagnosis and training, the role of patient involvement at a community level, as well as the assessment of the results of different initiatives in the field.